(untitled) (Medical Forum Monthly, 2024)
Background: Congenital malformations are the leading cause of neonatal mortality and morbidity. Out of all birth defects, congenital abnormalities of the heart are at the top. There are many etiological factors responsible for such defects. Environmental agents or teratogens are the factors which could be detected by certain screening methods and may be controlled at an early stage to minimize the chance of mortality. This study was conducted to detect the efficacy of inovo culture system as screening system for teratogenecity testing. Study Design: Experimental study. Place and Duration of Study: This study was conducted at the Department of Anatomy, Isra University Hyderabad for a period of six months. Materials and Methods: White Leghorn Chicken eggs were incubated for 3 days and after 3 days eggs were injected with ethanol 10% and 20%, PBS, neutral red dye and some were left untouched. The eggs were again incubated back until day 9. On day 9 the embryos were taken out and examined for gross malformations. The hearts were then fixed and processed for H&E staining and examined under microscope. Results: The results showed that addition of alcohol (ethanol) to chicken eggs produced many gross malformations and examination of hearts under microscope also showed malformed hearts. However other chemicals used did not show any malformations. Conclusions: This study confirmed the teratogenecity of ethanol in chick embryos and can be used as an alternative method for screening of teratogens and toxins.